Effect Factor of Arsenite and Arsenate Removal by a Manufactured Material: Activated Carbon-Supported Nano-TiO2. (18th September 2020) - Luo, Qian; Li, Gang; Chen, Meifeng; Qin, Fanxin; Li, Haiyan; Qiang, Yu
Abstract : Carbon substrate-supported nano-TiO2 (a manufactured material) was prepared in this study for arsenic removal. The removal rates of arsenic were evaluated by batch tests under several simulation conditions including pH, ionic strength, and adsorbent dosage. Results showed that As(III) and As(V) adsorption reached equilibrium within 10 hours (pH = 8 and ionic strength 0.5 mol/L). At pH = 8, maximum adsorption efficiency was discovered for the adsorbent. Removal rate was proportional to the increase in ionic strength. The removal data were satisfactorily fitted to the pseudo-second-order kinetic model ( R 2 > 0.9990) and Freundlich equation ( R 2 ≥ 0.9600) for adsorption thermodynamic behaviors. New material showed more effective adsorption performance for As(V) than for As(III). It was found that 15.1800 mg/g As(V) and 13.3800 mg/g As(III) were adsorbed, respectively. In addition, material properties were studied including the structure of crystallinity, surface morphology, functional groups, and surface texture by XRD, TEM/SEM, FTIR, and BET methods, respectively. XRD result showed supported nano-TiO2 had the anatase phase. The size of the microparticle was around 52 nm. BET results indicated that material surface areas, pore volume, and pore size diameter were 371.17 m 2 /g, 0.35 cm 3 /g, and 11.70 nm, respectively. FTIR spectrum indicated that several functional groups (OH −, Ti-O) existing in supported nano-TiO2 may facilitate the adsorption efficiency. Mechanistically, supported nano-TiO2 played a key role in promoting adsorption efficiency and converting As(III) to As(V). Results indicated that the investigated adsorbents possessed an excellent arsenic removal capability.